Sociodemographic differences in the use of dietary supplements in a representative sample of adults in Poland—a secondary analysis - Sierpiński, Radosław; Jankowski, Mateusz; Raciborski, Filip; Kamińska, Agnieszka (Frontiers in Nutrition, 2025)
IntroductionDietary supplements are concentrated sources of vitamins, minerals, or other substances with nutritional or physiological effects. This study aimed to assess sociodemographic differences in the use of dietary supplements in a representative sample of adults in Poland.MethodsThis is a secondary analysis of a dataset generated during the representative cross-sectional survey (December 2024) carried out among 5,006 adults aged 18–64 years in Poland. Attitudes towards the use of dietary supplements were assessed.ResultsAmong all respondents (n = 5,006), 39.1% reported regular use of dietary supplements in the 3 months preceding the present study, and another 31.5% reported occasional use. Among those who used supplements in the 3 months preceding the study, 11.4% had all of their supplements prescribed by a doctor, and another 22.7% had some of them. The highest prevalence of dietary supplement use was among those following a low-carbohydrate diet (58.4% regular and 27.9% occasional use), and the lowest among those who reported not paying much attention to their diet (24.9% regular and 32.2% occasional use). In multivariable logistic regression, female gender, younger age, secondary educational level, place of residence (living in cites <100,000 residents of cities > = 500,000 residents), having at least 3 infections per year, lack of significant interest in own diet, and diet with restrictions on carbohydrate intake were significantly associated (p < 0.05) with higher odd of the regular use of dietary supplements in the last 3 months preceding the survey.ConclusionThis study revealed that the majority of working-age adults in Poland use dietary supplements, but only one-third of dietary supplement users consult with a doctor. Gender, age, educational level, place of residence, health status, and diet-related behaviors were significantly associated with attitudes towards the use of dietary supplements. There is a need for educational activities in the field of nutritional education and building public awareness about the indications for the use of dietary supplements.